No evidence for increased habitual or decreased goal-directed action control after acute stress - Katharina Zwosta; Tatjana Karcz; Marcus Möschl; Moritz Walser; Thomas Goschke; Hannes Ruge; Uta Wolfensteller (PLoS ONE, 2025)
Previous studies suggested that acute stress can impair flexible goal-directed action control in favor of habitual action control. In addition, there is evidence that acute stress differentially affects the processing of rewards and punishments. Therefore, we aimed at investigating whether acute stress affects the balance between goal-directed and habitual behavior not only for behavior aiming at reward but also for behavior motivated by avoiding punishments. In two experiments, a total of 129 participants either underwent a standardized procedure to induce acute stress or a control procedure. Habitual approach and avoidance behavior was established by extensively training participants on responses resulting in either gaining a monetary reward or avoiding a monetary loss. Subsequently, the strength of the resulting habits was tested in the habit-goal competition task. We found no evidence for acute stress to influence the acquisition of novel behaviors or the resulting habit strength, neither for approach nor for avoidance behavior. This result remained when inter-individual differences in cortisol reactivity and subjective reports of chronic stress were taken into account. Together, our results speak against a general effect of acute stress boosting the behavioral impact of habitual behavior on goal-directed action control.